PENGARUH SUSUNAN PIPA LALUAN TERHADAP PEMANFAATAN KALOR PADA KOLEKTOR SURYA PELAT DATAR ABSORBER GRANITE - Made Wirawan; M. Mirmanto; I Gede Bawa Susana; Rudy Sutanto (Universitas Mataram, 2015)
The collector of solar energy can be used for heating fluidssuch as liquid or gas. The optimize absorbtion of solar energy depends on the collectordimention and component, e.g.the width, body of collector, tube formation, cover and isolation system. This research usesa granite absorber with a variation of tube formations and water flow rates. The aim of the research is tofind out the optimal tube formation. To achieve the aim of the research,theexperiments of water heating usingthree collectorswith a granite absorber 80 Cm x 100 Cm and three way tube formatians have been done.The variation of water flow rates had beenperformed toinvestigate the maximal performance. The water flow rates used were200, 250 and 300 cc/minute.The result of research achieved value of heat utilization of solar collector influenced by: arrangement inlet tube, flow rates of water and time. The maksimal heat utilization occur at parallel 7 for each flow rate. The flow rate 300 cc/minute show maximal heat utilization.